Peran Negara Dalam Pengelolaan Ekonomi Menurut Al Qur’an - Nurhayati, Nurhayati; Jamal, Khairunnas (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This paper discusses the role of the state in managing the economy from the perspective of the Koran. In the Qur'an, there are clear guidelines regarding the state's responsibility to manage economic resources fairly and sustainably. The state has a strategic position in various aspects of the economy, such as community empowerment, regulating market and transaction mechanisms, managing natural resources, protecting vulnerable groups, and realizing equitable economic development. The Qur'an emphasizes the importance of the principle of social justice, where the state must ensure equal distribution of wealth through redistribution policies. The state also has the responsibility to manage natural resources wisely without over-exploitation, as well as guaranteeing the economic rights of vulnerable groups. In addition, the Qur'an reminds us that economic development must not only focus on aspects of material growth, but must also improve the welfare of the entire community. Overall, this paper emphasizes the significant role of the state in managing the economy based on the moral and ethical principles taught in the Koran, in order to achieve justice and shared prosperity.